EARLY RHEUMATOID ARTHRITIS: CURRENT ASPECTS OF ITS DIAGNOSIS AND TREATMENT - Yu A Olyunin; Yu A Olyunin (Современная ревматология)
Progression of rheumatoid arthritis (RA) leads to the generalization of a pathological process, by involving new joints and extra-articular structures, the formation of irreversible changes, and resistance to performed therapy. The most favorable conditions for its treatment are available at the onset of the disease in the patients who have not received basic anti-inflammatory therapy. Therefore the solution of practical issues of medical care to patients with early-stage RA is quite urgent. It is necessary to decide as soon as possible whether basic anti-inflammatory drugs (BAIDs) should be used in patients with verified RA or at real risk for its development. Preference is usually given to conventional BAIDs at the first stage of therapy. Till recently methotrexate (MT) has been the gold standard treatment of such patients. However, the latest guidelines of the American College of Rheumatology for the use of biological and non-biological BAIDs recommend that MT of leflunomide (LF) should be given at a physician's discretion. The standard scheme for using LF in graded doses makes it possible to provide the therapeutic blood concentration of the drug just within the first week of therapy and a noticeable clinical improvement within the first month. So LF acts much more rapidly than other conventional BAIDs and may be of particular interest in treating RA.